Formulasi Sediaan Sabun Mandi Padat Dengan Zat Aktif Ekstrak Kulit Buah Alpukat (Persea Americana MILL) - Zaenal Fanani; Vivin Rosvita; Nur Aisah; Novam Danu Pamungkas; Ilun Fadillah (Universitas Muhammadiyah Klaten, 2021)
Avocado peel contains alkaloids, flavonoids and saponins, where these compounds have potential as antibacterial. This study aims to utilize avocado peel extract in the form of bath soap which has the potential to remove dirt, dead skin cells, dull skin amd prevent skin irritation. By paying attention to formula for the solid soap, in terms of addition 3 types of oil and variations in the concentration of coconut oil. This study used sample of avocado peel extract, Persea Americana Mill. The extraction method uses maceration, with 96% ethanol as solvent. Quality testing based on organoleptic, including (color, shape, and smell). Based on the pH value of soap, using universal indicator pH instrument. Quality testing also includes foam height and stability, moisture content, and free alkali which is carried out by the alkalimetric titration method. The pH value test results obtained an average of 10.6, so that it meets SNI 2016 which is 99-11. Testing the foam height with an average of 2.23 cm, so that it meets SNI 2016 which is 1.3-22 cm. Foam stability obtained an average of 25.62%, so that it meets SNI 2016 which is 60-70%. The moisture content obtained an average of 14.3%, so that it meets SNI 2016 which is maximum of 15%. And the alkali value obtained an average of 0.53%, does not meet SNI 2016 because the maximum alkali value is 0.1%.